Rethinking sustainable cities: Accessible, green and fair - Simon, David (Policy Press, 2016)
Available Open Access under CC-BY-NC licence. Sustainable urbanisation has moved to the forefront of global debate, research and policy agendas over recent years. Rapid urbanisation throughout China, India and many other low and middle income countries poses new challenges both locally and internationally at a time when urban areas worldwide are threatened by climate/environmental change. This compact book is designed to make a signal contribution to the sustainable urbanisation agenda through authoritative interventions contextualising, assessing and explaining clearly the relevance and importance of three central characteristics of sustainable towns and cities everywhere, namely that they should be accessible, green and fair. These three terms form key tenets of the work of Mistra Urban Futures (MUF; http://www.mistraurbanfutures.org/en), an international research centre on sustainable urbanisation based in Gothenburg, Sweden, and working through transdisciplinary research platforms there, in Greater Manchester (UK), Cape Town (South Africa) and Kisumu (Kenya). Additional platforms are being established in southern Sweden, Asia and Africa.